Neoadjuvant treatment with lenvatinib and pembrolizumab in a BRAF V600E-mutated anaplastic thyroid cancer: a case report - Barbaro, Daniele; Forleo, Raffaella; Profilo, Maria Antonietta; Lapi, Paola; Giani, Carlotta; Torregrossa, Liborio; Macerola, Elisabetta; Materazzi, Gabriele (Frontiers in Endocrinology, 2024)
Background Tyrosine kinase inhibitors (TKIs) and immunotherapy have been proposed for advanced metastatic anaplastic thyroid cancer (ATC). We report a case of BRAF V600E-mutated ATC in which lenvatinib (L) plus pembrolizumab (P) enabled neoadjuvant treatment. Case presentation A male patient aged 65 years presented with a rapidly enlarging left latero-cervical mass. Fine needle aspiration was suggestive of ATC. Surgical consultation excluded radical surgery. While awaiting molecular profile analysis and considering the fast evolution of the disease, treatment with L and P was started. L was started at a dose of 14 mg daily, while P was started at the standard regimen (200 mg every 3 weeks). After 1 month, computerized tomography showed a reduction in the mass with almost complete colliquative degeneration, and the carotid artery wall was free from infiltration. Radical surgery was performed. Histology confirmed papillary thyroid cancer (PTC) in the left lobe and ATC with extensive necrosis in the left latero-cervical lymph node metastasis. The margins were free of tumors (R0). A BRAF V600E mutation was present in both PTC and ATC. At the 1-year follow-up, the patient was free of disease. Conclusion L and P in combination also appeared to be effective as a neoadjuvant treatment for BRAF V600E-mutated ATC. This combination treatment could be used when there is an opportunity for complete resection of the cancer, and as soon as possible. The intermediate dose of 14 mg of L appeared to be well tolerated and effective.